SABINA'S STRUGGLE TO GET SELF-ACTUALIZATION IN DANIELLE STEEL'S SECRETS: A HUMANISTIC PSYCHOLOGICAL APPROACH - ASTUTI, NOVI DWI (2007)
This study concerns with the novel entitled Secrets, which is written by Danielle Steel. The analysis of this research paper is focused on how the major character's struggle to get self-actualization is reflected in the major character, namely Sabina Quarles based on its structural elements and humanistic psychological approach. The researcher uses a qualitative method whose data are based on primary source, the novel Danielle Steel's Secrets itself and secondary source, such as Danielle Steel's biography and other data dealing with the research. The data collection is documentation and technique of data collection is descriptive. The result of this study is as follows: firstly, the structural elements of the novel present a unity. It appears in the exposition, complication, climax, and resolution of the story. Secondly, the humanistic psychological approach shows that basic needs are the needs owned by every human being that are urgent to be fulfilled. The basic needs appear in inner sense as a motivation of human activities to struggle.